The language of the weather forecast in Italian and Spanish television broadcasts: Linguistic-descriptive analysis of the end of winter on RTVE and TG5 television channels - Vallejo, Rubén González (East European Journal of Psycholinguistics, 2023)
Weather information is of great importance to society due to the impact of the physical environment on everyday life. As a result, popular tradition has disseminated many proverbs related to human activities that have been the subject, over time, of scientific studies, intending to verify the veracity of such predictions. For this reason, this article initially presents a brief bibliographical and regulatory analysis of the evolution of atmospheric language and a presentation of the bodies that regulate its communication in Spain and Italy. Subsequently, a corpus of weather reports extracted during December 2022 from an Italian and Spanish news channel will be illustrated to study the communication of weather forecasts from a macro- and microstructural linguistic level, given the need for studies in both languages. For this purpose, Speechnotes will be used for the transcriptions, and Sketch Engine to create the corpus. As a result of the analysis, Spanish news programmes devote more time to the space of time, show a much higher speed of locution than the Italian corpus, provide a more significant number of mechanisms to show probability and uncertainty, and a great variety of linguistic-discursive strategies to exemplify the scientific context. We also find a recurrent gerund, which we will call an "atmospheric gerund". In Italian, on the other hand, we find greater deixis, more synthetic information, and less dynamism in the interaction with the data. Funding Statement This work has been funded by the Margarita Salas grants for the training of young doctors (2021-2023) of the University of Salamanca. Author: Rubén González Vallejo, 0000-0002-9697-6942 u156528@usal.es